IMPLEMENTATION OF NON-DISCRIMINATION IN RESPECT TO DETERMINE THE APPROPRIATE POLICY FOR DEALING WITH INTERNATIONAL TRADE (UUM Journal of Legal Studies, 2020)
International trade is an activity involving the exchange of goods and services across national borders. International trade is strongly influenced by the harmonization of political, legal, social and cultural rights owned by respective countries. A number of principles have been formulated and enforced to prevent and resolve disputes arising from international trade, one of which is the principle of non- discrimination. In practice the existence of the principle of non-discrimination often cannot be implemented, because it runs contrary to the policies of each country which is to protect its own interests. Based on the background of the problem that has been described, three subject matters were identified: 1. How can the principle of non-discrimination be applied in international trade? 2. How can appropriate legal policies in dealing with the negative impact of international trade be determined? 3. How can expected disputes on international trade be resolved? The method used in this study was the normative juridical approach to literature. Studies have properties that descriptive analytical assessment phase which focuses on the assessment of secondary data. Data was collected by means of a literature study to support the object of assessment. The results of the assessment conducted revealed that the principle of non-discrimination in international trade cannot be directly applied. Although there is a variety of policies whether committed by the government or society which indirectly consider the principle of non-discrimination internationally, the principle of non-discrimination can only be applied if it can support and protect the interests of concerned parties.